2020
DOI: 10.1002/aenm.202002676
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating and Mitigating Degradation Processes in Perovskite Light‐Emitting Diodes

Abstract: cells, lasers, detectors, and light-emitting diodes (LEDs) owing to their exceptional optical and electronic properties such as long charge-carrier diffusion lengths, high absorption coefficients, tunable bandgaps, and facile processing. [1-4] For bulk polycrystalline perovskite thin films, one of the key approaches to boost the stability and optoelectronic properties is through employing mixtures of A-site cations, such as methylammonium (MA), formamidinium (FA), and cesium (Cs) [5,6] as well as mixtures of X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…Films containing PMAI additive exhibit small grain sizes of < 20 nm (Figure 4g), while larger grain sizes are found for the stoichiometric MAPbI 3 films (50-195 nm) and films containing KI additive feature larger grain sizes (70-220 nm) (Figure 4a,d). It has been established that the KI additives can efficiently passivate defects and reduce first-order defect-assisted nonradiative recombination in perovskites, [27][28][29][30][31] while the PMAI additives can both passivate defects and enhance electron-hole capture rate at low current density (e.g., < 100 mA cm −2 ). [4,19] On the other hand, the influence of perovskite compositions corresponding current pulses shown in Figure S5, Supporting Information.…”
Section: Transient El Dynamics Of Perovskite Ledsmentioning
confidence: 99%
“…Films containing PMAI additive exhibit small grain sizes of < 20 nm (Figure 4g), while larger grain sizes are found for the stoichiometric MAPbI 3 films (50-195 nm) and films containing KI additive feature larger grain sizes (70-220 nm) (Figure 4a,d). It has been established that the KI additives can efficiently passivate defects and reduce first-order defect-assisted nonradiative recombination in perovskites, [27][28][29][30][31] while the PMAI additives can both passivate defects and enhance electron-hole capture rate at low current density (e.g., < 100 mA cm −2 ). [4,19] On the other hand, the influence of perovskite compositions corresponding current pulses shown in Figure S5, Supporting Information.…”
Section: Transient El Dynamics Of Perovskite Ledsmentioning
confidence: 99%
“…[114] On the other hand, irreversible accumulation of ions at an interface is observed in mixed halide PeLEDs, leading to charge-carrier injection barriers and nonradiative recombination. [129] The low formation energy of perovskite materials and the complex electrochemistry at the device interfaces remain big concerns for commercial lightemitting applications. [130,131] It is widely known that halide perovskites suffer from photoinstabilities, showing both photobrightening and photodarkening effects.…”
Section: Device Stabilitymentioning
confidence: 99%
“…[ 133 ] This phenomenon is observed in EL leading to a “burn‐in” or “luminance overshoot” under operation attributed to ionic reorganization in perovskites that can be maintained for longer periods of operation with appropriate passivation. [ 129,134,135 ] Interestingly, some groups have taken advantage of this phenomenon to propose perovskite‐based light‐emitting electrochemical devices, [ 136 ] opening new avenues for these materials. [ 137 ] It remains to be seen if such approaches can stabilize operation over long periods, including mitigating against redox chemistry in these ionic systems in the presence of high densities of injected electrons under operating conditions—but such breakthroughs will be critical for realizing long‐term stability.…”
Section: Challenges and Outlookmentioning
confidence: 99%
“…[10,34,35] Numerous works have reported that the EQE of PeLEDs increases with the bias voltage, current density, and subsequent scans during the electric bias. [36][37][38][39][40][41] We usually observed that both magnitudes of the electroluminescence (EL) and efficiencies are very low while PeLEDs are operated at the low electric bias, but significantly increased at the high bias regime. [42,43] Such observations deviate the ideal current density-luminescence-voltage (J-L-V) characteristics for decent light-emitting diodes (LEDs) with a relatively high magnitude of EQE.…”
Section: Introductionmentioning
confidence: 99%